Manajemen Pendidikan Karakter Berbasis Kearifan Budaya Lokal Masyarakat Samin dalam Menghadapi Era Globalisasi - Putri, Septia Dwi Anggraeni; Sumarsono, Raden Bambang; Sunarni, Sunarni; Maisyaroh, Maisyaroh (Universitas Negeri Malang, 2024)
Abstract: Character education that is instilled in students can be related to local cultural wisdom so that it is not eroded by the increasingly advanced era of globalization. The purpose of this study is to review in depth the management of character education based on local cultural wisdom of the Samin community starting from planning, implementation, monitoring, and the inhibiting and supporting factors of character education management activities. This research method uses a qualitative approach to the type of research design through case studies. Data collection techniques were carried out by interviews, observation, and documentary studies. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The result of the research is that SDN Margomulyo II Margomulyo Sub-District holds an Annual School Work Plan which produces the P5 teaching module. The activities carried out to implement character education based on the local cultural wisdom of the Samin people are through bazaars (market day) which is held on Fridays and the Samin festival, namely poetry reading and writing competitions. There are inhibiting factors, namely the lack of discipline of students, ignoring teacher advice, and at home there are still those who do not obey their parents' orders, while the supporting factors are the native residents of Kampung Samin who have been taught aboutGreat Advice,